Venovenous extracorporeal membrane oxygenation for severe exogenous lipoid pneumonia induced by diesel aspiration - Ding, Yunyi; Zheng, Zhongjun; Wang, Haizhen; Qi, Wenqi; Lu, Xiao (Frontiers in Medicine, 2025)
This case report presents a novel application of venovenous extracorporeal membrane oxygenation (VV-ECMO) in the treatment of a patient with severe exogenous lipoid pneumonia caused by diesel aspiration. Although the patient ultimately died of septic shock, ECMO significantly improved lung function and the oxygenation index, demonstrating its potential as an innovative supportive treatment method for such severe respiratory diseases.